2014
DOI: 10.1007/s10973-014-4117-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of composite polyaniline/poly(vinyl alcohol)/palygorskite

Abstract: The preparation of composites occurred by insertion of organically modified molecules, using quaternary ammonium salts-Cetremide (cetyl trimethyl ammonium bromide, CTAB) and Genamim (cetyl trimethyl ammonium chloride, CTAC)-in the fibrous structure of the palygorskite clay (PALY). For the preparation of PANI/PVA (polyaniline/poly(vinyl alcohol), PANI/PVA/ PALY, PANI/PVA/PALY-CTAB, and PANI/PVA/PALY-CTAC films, the ''casting'' technique was used, and they were characterized by XRD, FTIR, SEM, TG/DTG, and DSC. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…Moreover, it was shown that the quality retention still can come to 53.54% when the temperature up to 400 °C. Based on above thermal decomposition analysis, it was confirmed that the poly(AMPS/AM/SSS) has excellent thermal stability …”
Section: Resultsmentioning
confidence: 85%
“…Moreover, it was shown that the quality retention still can come to 53.54% when the temperature up to 400 °C. Based on above thermal decomposition analysis, it was confirmed that the poly(AMPS/AM/SSS) has excellent thermal stability …”
Section: Resultsmentioning
confidence: 85%
“…Although dispersions contain colloidal particles instead of polymers, if we assume the dispersed water droplets slip past each other like the reptation motion of polymer chains the results of polymer analysis can be transferred to dispersions. It is observed that both dispersions present pseudoplastic liquid behaviour 47 . The viscosity of in situ PVA/PANI is higher at lower shear rate and then keeps decreasing with shear rate.…”
Section: Resultsmentioning
confidence: 92%
“…Hydrogels composed of polymers (chitosan and polyvinyl alcohol) were developed by [52], this paper evaluated the influence of the percentage of laponite in the hydrogels, noting the presence of the clays. [58], developed a dendrimer, in the form of nanodiscs, using laponite in its structure.…”
Section: Articles Researchmentioning
confidence: 99%
“…The interaction between the components of the biomaterial formulation (drug, clay and other constituents) will determine the way and the rate with the drug is released from the matrix. Some parameters directly influence the controlled release process, such as the effect of solubility,effect of PH [62,63], effect of clay quantity drug effect carried and kinetic study [4,45,58].…”
Section: Articles Researchmentioning
confidence: 99%